2018
DOI: 10.1002/hipo.22838
|View full text |Cite
|
Sign up to set email alerts
|

Theta frequency decreases throughout the hippocampal formation in a focal epilepsy model

Abstract: Mesial temporal lobe epilepsy is characterized by focal, recurrent spontaneous seizures, sclerosis and granule cell dispersion (GCD) in the hippocampal formation. Changes in theta rhythm properties have been correlated with the severity of hippocampal restructuring and were suggested as a cause of memory deficits accompanying epilepsy. For severe sclerosis, it has even been questioned whether theta band oscillations persist. We asked how theta oscillations change with graded restructuring along the longitudina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
35
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(43 citation statements)
references
References 86 publications
4
35
2
Order By: Relevance
“…The first hour of recordings was discarded (to avoid the exploration phase in the recording cage), artifacts were removed manually, discharges were automatically detected, based on a combination of frequency composition and amplitude threshold as described previously, 26,27 and results were visually verified. For analysis of recurrent EA (and baseline activity in controls), mice were preselected (see Methods S1; final numbers: n KA = 6 mice, n NaCl = 4 mice).…”
Section: Eeg Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The first hour of recordings was discarded (to avoid the exploration phase in the recording cage), artifacts were removed manually, discharges were automatically detected, based on a combination of frequency composition and amplitude threshold as described previously, 26,27 and results were visually verified. For analysis of recurrent EA (and baseline activity in controls), mice were preselected (see Methods S1; final numbers: n KA = 6 mice, n NaCl = 4 mice).…”
Section: Eeg Analysismentioning
confidence: 99%
“…Severe epileptiform events were classified according to the number of discharges, median interdischarge interval, and coefficient of variation using hierarchical clustering, as described previously. 27 A A1…”
Section: Eeg Analysismentioning
confidence: 99%
“…This theta power decrease has been described to be due, at least in part, to IA. Studies in TLE animal models confirmed the decrease in theta power (Arabadzisz, Antal, Parpan, Emri, & Fritschy, ; Chauvière et al, ) and frequency (Chauvière et al, ; Kilias et al, ) and suggest potential explanations. An impairment of the theta generators, either by modification of the theta pacemaker structure or by aberrant connections (e.g., sprouting) between theta oscillators (Christenson, Leintz, Xamonthiene, Huang, & Krook‐Magnuson, ; Dudek & Shao, ) was proposed, as well as a modification in the resonance features of neurons involved (Marcelin et al, ; Wolfart & Laker, ); for review see (Sharma et al, ).…”
Section: How Is Tl‐dependent Cognition Altered In Temporal Lobe Epilementioning
confidence: 86%
“…Hippocampal theta rhythm (4-12 Hz) plays a key role in cognitive processes in both humans and animals [1,2] and is associated with a variety of cognitively related behaviors, including spatial coding, memory and sniffing exploratory locomotion [3]. The decreased theta activity is correlated with cognitive deficit seen in neurodegenerative disease such as epilepsy and Alzheimer's disease (AD) [4,5,6,7].…”
Section: Introductionmentioning
confidence: 99%